THE EFFECTS OF SELF- AND PEER- CORRECTION TECHNIQUES ON STUDENTS’ WRITING COMPETENCY - Suci Laksmi Dewi Ni Kadek (Lingua Scientia, 2020)
The objectives of this research are 1) to prove the significant difference of the effect between self-correction and peer-correction techniques on students’ writing competency, 2) to prove the significant difference of the effect between self-correction and peer-correction technique on students’ writing competency across descriptive text, 3) to prove the significant difference of the effect between self-correction and peer-correction on students’ writing competency across recount text. The research applied a quasi-experimental research design with two groups. The sample recruited two intact classes using a purposive sampling, which totaled 60 students. Moreover, the two groups were assigned to different groups randomly. The obtained data were analyzed descriptively and inferentially. The result shows, firstly, the effect of peer-correction technique was more significant than self-correction technique on the students’ writing competency. Secondly, the effects of peer-correction technique were more significant than self-correction across descriptive text. Thirdly, the effects of peer-correction technique were more significant than self-correction across recount text. The result implies the necessity to apply the peer-correction than self-correction when the Junior High School students write English text types.Keywords: : self-correction, peer-correction, and text type